1997
DOI: 10.1038/sj.onc.1201314
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the rap1 signaling pathway are common in human gliomas

Abstract: Several inherited predisposition to cancer syndromes are associated with the development of nervous system tumors. Tuberous sclerosis complex (TSC) is an autosomal dominant disorder in which a ected individuals are at risk for developing astrocytomas. One of the genes responsible for this disorder is TSC2, located on chromosome 16p, and encoding a 180 kDa protein (tuberin) that functions in part as a negative regulator of rap1. Previous studies from our laboratory demonstrated that 30% of sporadic astrocytomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 10 publications
4
34
0
Order By: Relevance
“…Western blotting was performed using WA15a (pan neuro®bromin; Gutmann et al, 1996), tubulin (clone DM1-A; Sigma), GFAP (Zymed), and activation-speci®c phospho-MAPK and p38-MAPK (Promega) antibodies with HRPconjugated secondary antibodies (Sigma) and ECL development (Amersham). Primary antibodies were used according to the manufacturer's recommendations while WA15a was used at a 1 : 300 dilution (Basu et al, 1992;Norton et al, 1995a,b).…”
Section: Rna and Protein Analysismentioning
confidence: 99%
“…Western blotting was performed using WA15a (pan neuro®bromin; Gutmann et al, 1996), tubulin (clone DM1-A; Sigma), GFAP (Zymed), and activation-speci®c phospho-MAPK and p38-MAPK (Promega) antibodies with HRPconjugated secondary antibodies (Sigma) and ECL development (Amersham). Primary antibodies were used according to the manufacturer's recommendations while WA15a was used at a 1 : 300 dilution (Basu et al, 1992;Norton et al, 1995a,b).…”
Section: Rna and Protein Analysismentioning
confidence: 99%
“…Furthermore, we demonstrated levels of activated Ras.GTP also to be elevated in human GBM tumour specimens compared to normal brain specimens (Guha, et al, 1997). Ras activation in astrocytomas is not on the basis of inadequate Ras-GAP activity, since abundant levels of both p120-GAP and neuro®bromin, the two major mammalian Ras-GAPs, are found in these tumours (Gutmann et al, 1996). Transfection of the dominant inhibitory mutant H-Ras N17 (Feig and Cooper, 1988) to reduce Ras.GTP levels resulted in reduced anchorage-dependent proliferation and colony formation in soft agar (Guha, et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The tuberous sclerosis complex 2 protein product, tuberin, has been shown to function as a negative regulator of Rap1 (32). Previous work from our laboratory (32,33) has demonstrated that loss of tuberin expression is observed in 30% of sporadic astrocytomas. This loss of tuberin expression in astrocytic tumors, could result in increased cell proliferation as a result of elevated Rap1 activation.…”
Section: Figmentioning
confidence: 99%